CULTURAL LITERACY OF COASTAL FOLKTALES: CHARACTER EDUCATION AND STRATEGIES FOR THEIR INTEGRATION INTO LEARNING IN THE CITY OF SEMARANG - Nuryatin, Agus; Febriani, Meina; Agry, Feylosofia Putri; Hidayat, Sefiyan Eza Nur; Ariyanto, Ixora Maftuchah Pramudya (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program partners with SMA 14 Semarang, which is located in a coastal area and has strong potential to utilize coastal folktales as learning media. However, four key problems were identified: (1) teachers at SMA 14 Semarang have limited understanding of cultural literacy based on coastal folktales; (2) there is no available cultural literacy learning module grounded in coastal folktales; (3) teachers have minimal skills in using digital media to present coastal folktales in an engaging manner; and (4) there is a lack of intensive training for integrating cultural literacy across subjects, all of which require comprehensive solutions. Through this community service program, we aim to address these partner-related challenges comprehensively by leveraging science and technology (IPTEKS), in accordance with our expertise and available resources. To resolve these issues systematically, we conducted training sessions, developed learning modules, facilitated the use of digital technology, and provided mentoring in the implementation of cultural literacy based on coastal folktales in schools. The method employed was the Participatory Action and Learning System (PALS). The activities included education, training, counseling, capacity building, and mentoring, all collaboratively designed to ensure the effectiveness and sustainability of the program. The results indicate that integrating folktales into the curriculum enriches learning with meaningful local contexts, enhances students’ appreciation of cultural heritage, and fosters character values such as mutual cooperation, responsibility, and environmental awareness. In addition, teachers gained new insights and skills in designing project-based learning by utilizing the interactive modules developed during the program.